The dark side of Charles Darwin : a critical analysis of an icon of science - Bergman, Jerry (Green Forest, Ark. : Master Books, 2011)
A single man stands behind one of the greatest deceptions in history... Charles Darwin's ideas still penetrate every aspect of our culture, including science, religion, and education. And while much has been made of his contribution to the evolutionary hypothesis, little has been publicized about the dark side of the man himself and how this may have impacted the quality and legitimacy of his research. This daring and compelling book takes its readers behind the popular facade of a man revered worldwide as a scientific pioneer, and unveils what kind of person Darwin really was. The book reveals disturbing facts that will help you: Perceive Darwin firsthand through the eyes of family and friends, and his own correspondence, Discern this darkly troubled man, struggling with physical and mental health issues, Uncover his views on eugenics and racism, and his belief that women were less evolved than men. Thoroughly documented, this book reveals Darwin's less-than-above board methods of attempting to prove his so-called scientific beliefs, and his plot to "murder God" by challenging the then-dominant biblical worldview.
Darwin and Christianity. how Darwin overthrew creationism among the intellectual establishment ; Why Darwinism demands atheism ; Darwin's religious views ; Darwin's religion of purposelessness -- Darwin and mental health. What Darwin psychotic? A study of his mental health ; Were Darwin's mental health problems due to his conflicts with theism? ; Darwin's passion for hunting and killing -- Darwin and his theory. Did Darwin plagiarize his evolution theory? ; Darwin's faulty scholarship--a review ; Pangenesis: Darwin's now disproved theory -- Darwin, racism, and sexism. Was Darwin a racist? ; Darwin inspires eugenics ; Darwin's view of women ; Darwin was wrong: natural selection cannot explain macro-evolution.
Includes bibliographical references.
Keywords: Darwin, Charles, -- 1809-1882.; Evolution (Biology); Natural selection